(3LfGjI GdJChjd GdaGSO Ydi GdYbjOI GdESdGejI (B/s - (3dhM, eMeO CMeOs (Saudi Arabia : Dar Ibn'Affan, 1997)
The imperfection of interpretation; Islamic doctrines
Keywords: Qur'an -- Criticism, interpretation, etc. -- History; Islam -- Doctrines -- History; Philosophy, Islamic -- History